Rancang Bangun Aplikasi Forum Diskusi Pelaut Berbasis Android Menggunakan Metode Extreme Programming di PT Azure Samudera Karsa - Soni Ayi Purnama Purnama (Masoem University, 2026)
The need for rapid and structured maritime information exchange within PT Azure Samudera Karsa necessitates a reliable digital communication platform for the seafarer community. This study aims to design and implement a Seafarer Discussion Forum Application using the User-Centered Design approach. The system was developed using the Extreme Programming) methodology, utilizing a Laravel 12-based backend architecture and a Flutter frontend to ensure responsive performance, adaptability to changing requirements, and high-quality coding standards. The research methodology encompasses requirements analysis, system design, iterative coding, and comprehensive testing, including Alpha Testing for functional validation and Beta Testing using the End-User Computing Satisfaction method to evaluate user satisfaction. The results demonstrate that the system operates stably, achieving a user satisfaction score of 84.52%, which indicates a